The genetic and cultural impact of the Steppe migration into Europe - Gabriele Scorrano; Fulya Eylem Yediay; Thomaz Pinotti; Motahareh Feizabadifarahani; Kristian Kristiansen (Taylor & Francis Group, 2021)
Background During the early 3rd millennium BCE migration from Pontic Steppe, mainly related to Yamnaya culture, has affected European populations both culturally and genetically, however, it has long been debated to what extent this migration was male-driven, and how this replacement process took place which eliminated partially/largely Neolithic male lines over time. Aim This paper aims to evaluate the influence of the Steppe migration on European Bronze Age populations by calculating both male and female genetic contributions of the Steppe-related ancestry to the European Bronze Age populations. With this approach, we will be able to clarify the hypotheses on whether it was male-biased migration or not. Subjects and methods To evaluate the genetic impact and the proportion of the Steppe-related ancestry to the European Bronze Age populations, we performed PCA and qpAdm analyses by using published genome-wide data. In addition, we quantified male and female genetic contribution into Europe by using the analysis of uniparental markers and the X-chromosome. Results The Steppe migration had a considerable impact on the genetic makeup of the Bronze Age European populations. The data suggest that the Steppe-related ancestry arriving into Central Europe was male-driven, dominantly in the Corded Ware culture populations and lesser in the Bell Beaker populations. In fact, there is no evidence that this migration had a significant input on the mitochondrial genetic pool of all European Bronze Age populations. Conclusions Our analyses suggest that the Steppe-related ancestry had genetic impact on mainly Central-Eastern Europe. Moreover, this migration was male-driven for most of the Central European populations belonging to the Corded Ware groups, and to a lesser extent for the Bell Beaker groups.